Neuronal-Activated ILC2s Promote IL-17A Production in Lung γδ T Cells During Sepsis - Chen, Weiwei; Lai, Dengming; Li, Yuehua; Wang, Xueke; Pan, Yihang; Fang, Xiangming; Fan, Jie; Shu, Qiang (Frontiers in Immunology, 2021)
Studies have revealed important roles for IL-17A in the development of acute lung injury (ALI) following sepsis. However, the mechanism underlying the regulation of lung IL-17A remains to be fully addressed. Recent studies suggested the effect of neuromedin U (NMU) on immune cell activation and the role of group 2 innate lymphoid cells (ILC2s) in the modulation of IL-17A production. We aimed to gain in-depth insight into the mechanism underlying sepsis-induced lung IL-17A production, particularly, the role of NMU in mediating neuronal regulation of ILC2s and IL-17A-producing γδ T cells activation in sepsis. Wild-type mice were subjected to cecal ligation and puncture (CLP) to induce sepsis with or without intraperitoneal injection of NMU. The levels of ILC2s, γδ T cells, IL-17A, NMU and NMU receptor 1 (NMUR1) in the lung were then measured. In order to determine the role of NMU signaling in ILC2 activation and the role of ILC2-released IL-9 in ILC2-γδ T cell interaction, ILC2s were sorted, and the genes of nmur1 and il9 in the ILC2s were knocked down using CRISPR/Cas9. The genetically manipulated ILC2s were then co-cultured with lung γδ T cells, and the levels of IL-17A were measured. In septic mice, the levels of NMU, IL-17A, ILC2s, and IL-17A-producing γδ T cells in the lung are significantly increased, and the expression of NMUR1 in ILC2s is increased as well. Exogenous NMU further augments these increases. The main source of IL-17A in response to CLP is γδ T cells, and lung nmur1 is specifically expressed in ILC2s. In vitro co-culture of ILC2s and γδ T cells leads to increased number of γδ T cells and higher production of IL-17A from γδ T cells, and these alterations are further augmented by septic treatment and exogenous NMU. Genetic knockdown of nmur1 or il9 in ILC2s attenuated the upregulation of γδ T cells and IL-17A production. In sepsis, NMU acting through NMUR1 in lung ILC2s initiates the ILC2 activation, which, in turn, promote IL-17A-producing γδ T cell expansion and secretion of IL-17A. ILC2-derived IL-9 plays an important role in mediating γδ T cell expansion and IL-17A production.